Informative Inhibiting Factors For Teachers In Implementing The Independent Curriculum At SMK Negeri 2 Sungai Penuh - Risha Febriyanti; Suharry; Nizwardi Jalinus (AKADEMI TEKNIK ADI KARYA, 2024)
The purpose of this study is to describe the factors that become obstacles in implementing the independent curriculum at SMK Negeri 2 Sungai Penuh. The method used in this study is descriptive qualitative research. The sample of this study was a subject teacher who taught in class X of SMK Negeri 2 Sungai Penuh. From the results of the study, it is known that the factos and obstacles felt by teachers consist of 3 stages, namely the planning stage, the implementation stage and the assessment stage.